Copolymer polyester sealant film
A laminated film with a concentration gradient of dicarboxylic acid components in its layers addresses the issues of low heat seal strength and recycling challenges in polyester packaging materials, providing enhanced adhesion and mechanical properties.
Patent Information
- Application Number
- JP2021067060
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-16
- Filing Date
- 2021-04-12
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-04-12
AI Technical Summary
Conventional polyester-based packaging materials face challenges in achieving high heat seal strength, compatibility with other materials, and difficulty in recycling due to the use of polyolefin-based resins, which result in low heat seal strength and adsorption of packaging contents.
A laminated film structure with a concentration gradient of dicarboxylic acid components, comprising a seal layer, intermediate layer, and outermost layer, where each layer contains a copolymerized polyester with varying ratios of dicarboxylic acid components, enhancing adhesion and heat seal strength.
The laminated film achieves excellent heat seal strength, mechanical properties, and facilitates recycling by ensuring compatibility with polyester materials, reducing adsorption of packaging contents, and maintaining transparency.
Smart Images

Figure 0007622527000001 
Figure 0007622527000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolymer polyester sealant film. [Background technology]
[0002] Polyester has excellent properties such as heat resistance, weather resistance, mechanical strength, transparency, chemical resistance and gas barrier properties, and is also readily available at a reasonable price, making it a highly versatile resin that is currently widely used in beverage and food containers, packaging materials, molded products, films, and more.
[0003] In recent years, environmental problems such as global warming have become serious, and packaging materials such as packages are being made more compact, and there is a demand for promoting recycling in order to reuse used packaging materials as resources. On the other hand, conventional packaging materials use a biaxially oriented film as a base film, and a film laminate obtained by heat sealing or laminating a sealant film to this as the innermost layer, and various functions such as storage stability are imparted by combining multiple materials with different properties, which has the problem of making them difficult to recycle.
[0004] For example, in a conventional packaging material, a non-stretchable sealant film made of a polyolefin resin as disclosed in Patent Document 1 is used as a sealant layer of the packaging material. Polyolefin resins such as polyethylene and polypropylene are known to have excellent heat sealability and high adhesion.
[0005] However, although unstretched sealant films made of polyolefin resins have excellent heat seal strength between polyolefin films, they have the problem of low heat seal strength with films made of other materials such as polyester. Another problem is that the material has a high affinity with the aroma and medicinal ingredients of the packaged contents, resulting in the adsorption of the ingredients.
[0006] In view of such problems, Patent Document 2 discloses a polyester film in which sealing properties are imparted to polyethylene terephthalate (PET). These polyester films for sealant applications have the advantage that they are less likely to adsorb components of the package contents due to their low affinity with various organic compounds. Furthermore, by laminating other polyester-based base films such as transparent barrier vapor-deposited PET, or by combining high barrier vapor-deposition and printing processing technologies with polyester-based films, it is possible to realize packaging materials made from a single material system consisting of polyester, which is expected to be highly recyclable.
[0007] However, in the case of a single-layer film as described in Patent Document 2, even if the content of the copolymerization component is increased in order to increase the heat seal strength, the melting point is lowered, so that the heat setting temperature during film formation cannot be increased, making it difficult to achieve high seal strength.
[0008] In view of such problems, Patent Document 3 discloses a multilayer polyester film for sealant use in which a layer having heat sealability is separated from other layers, and the content of copolymerization components in each layer is further varied.
[0009] However, the polyester film for sealant use described in Patent Document 3 has low sealing strength and does not satisfy market demands. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2002-256116 A [Patent Document 2] International Publication No. 2014 / 175313 Brochure [Patent Document 3] Patent No. 6724447 Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a copolymer polyester sealant film having extremely excellent heat seal strength and excellent recyclability. [Means for solving the problem]
[0012] As a result of intensive research, the present inventors have found that in a laminate film having heat sealability, excellent heat seal strength can be achieved by adopting a lamination structure in which the content ratio of copolymerization component in the heat seal layer gradually decreases in the thickness direction of the film from the heat seal layer to the outermost layer. The present invention has been completed based on these findings and has the following aspects.
[0013] [1] A first aspect of the present invention is a laminated film consisting of at least two layers having a seal layer and an outermost layer, each layer containing a copolymer polyester consisting of a copolymer of terephthalic acid and other dicarboxylic acid components, and a diol component, and the laminated film has a laminated structure in which the content (mol%) of other dicarboxylic acid components in each layer decreases from the seal layer to the outermost layer, and the laminated film has a heat seal strength of more than 25 N / 15 mm when sealed at 0.2 MPa for 1 second in the range of 160 to 200°C.
[0014] [2] In the above [1], it is preferable that an intermediate layer consisting of at least one layer is provided between the sealing layer and the outermost layer.
[0015] [3] In the above [2], it is preferable that the intermediate layer contains a copolymer polyester consisting of a copolymer of terephthalic acid and other dicarboxylic acid components and a diol component, and that the content (mol %) of the other dicarboxylic acid components contained in the sealing layer is higher than the content (mol %) of the other dicarboxylic acid components contained in the intermediate layer.
[0016] [4] In the above [2] or [3], the content (mol %) of the other dicarboxylic acid component contained in the intermediate layer is preferably the same as or higher than the content (mol %) of the other dicarboxylic acid component contained in the outermost layer.
[0017] [5] In any one of the above [2] to [4], the intermediate layer preferably contains polyethylene terephthalate.
[0018] [6] In any one of the above [1] to [5], the other dicarboxylic acid component preferably includes isophthalic acid and / or sebacic acid.
[0019] [7] In any one of the above [1] to [6], the outermost layer preferably contains inorganic particles.
[0020] [8] In any one of the above [1] to [7], the outermost layer preferably contains polyethylene terephthalate.
[0021] [9] A second aspect of the present invention is a laminate having, as at least one layer, the copolymer polyester sealant film according to any one of the above [1] to [8].
[0022]
[10] A third aspect of the present invention is a packaging material having at least a portion thereof the laminate described in [9] above. Effect of the Invention
[0023] The copolymer polyester sealant film of the present invention sufficiently exhibits the low shrinkage property and mechanical properties such as breaking strength and puncture strength required for sealant applications. Furthermore, the copolymer polyester sealant film of the present invention has extremely excellent heat seal strength. Therefore, the copolymer polyester sealant film of the present invention can be suitably used as a packaging material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] An example of an embodiment of the present invention will be described below, however, the present invention is not limited to the embodiment described below.
[0025] <This sealant film> A copolymer polyester sealant film according to an embodiment of the present invention (hereinafter, referred to as "the sealant film") is a laminated film having a seal layer and an outermost layer. An intermediate layer may be provided between the seal layer and the outermost layer. Each layer contains a copolymer polyester made of a copolymer of terephthalic acid and other dicarboxylic acid components and a diol component.
[0026] This sealant film has a laminated structure in which the content (mol %) of other dicarboxylic acid components in each layer decreases in the thickness direction of the film from the seal layer to the outermost layer, and when an intermediate layer is provided, the content (mol %) of other dicarboxylic acid components in the intermediate layer and the outermost layer may be the same. The method for providing a concentration gradient of the other dicarboxylic acid component in the thickness direction of the film is not particularly limited, but may include a method of laminating two or more layers having different contents of the other dicarboxylic acid component in the thickness direction. Whether or not the sealant film has a concentration gradient of the dicarboxylic acid component in the copolymer polyester in the thickness direction of the film can be confirmed, for example, by the presence or absence of an inflection point in the dicarboxylic acid concentration gradient in the thickness direction of the film. The inflection point can be investigated by creating an oblique cut surface of the film using SAICAS (registered trademark) and obtaining negative secondary ion peak intensity data using a time-of-flight secondary ion mass spectrometer TOF-SIMS.
[0027] The mechanism for achieving extremely excellent heat seal strength by creating a concentration gradient of the other dicarboxylic acid component in the thickness direction of the film is estimated as follows. When the above-mentioned concentration gradient is created, it is estimated that the crystal structures between adjacent layers become similar and interact more strongly, thereby preventing delamination between layers due to improved adhesion between layers. On the other hand, when there is no concentration gradient in one direction, delamination is likely to occur between the layer with the least amount of the other dicarboxylic acid component and the adjacent layer. In addition, for example, when the copolymerized polyester-based sealant film has a three-layer structure (A layer / B layer / C layer) where the A layer is the seal layer, the B layer is the intermediate layer, and the C layer is the outermost layer, when the content relationship of the other dicarboxylic acid component in each layer is A layer > B layer > C layer, compared with the cases of A layer > B layer and B layer < C layer, the force is propagated smoothly during the peeling process when measuring the heat seal strength. As a result, this sealant film can obtain extremely excellent heat seal strength.
[0028] This sealant film may be an unstretched film (sheet) or a stretched film. Among them, a stretched film stretched in the uniaxial direction or the biaxial direction is preferably used. Among them, a biaxially stretched film is preferably used in terms of excellent balance of mechanical properties and flatness.
[0029] <Seal layer> The seal layer is a layer containing copolymerized polyester A as the main component resin.
[0030] In the present invention, the main component resin means the resin with the highest content ratio among the resins constituting the layer. The main component resin may occupy 50% by mass or more, among which 70% by mass or more, and among which 80% by mass or more (including 100% by mass) of the resins constituting the layer.
[0031] The seal layer may consist only of copolymerized polyester A, but preferably contains a resin B other than copolymerized polyester A. The case where the sealing layer contains the copolymer polyester A and the resin B will be described later.
[0032] (Copolyester A) The copolymer polyester A is preferably a copolymer polyester which is a copolymer of terephthalic acid and other dicarboxylic acid components with a diol component.
[0033] Examples of the "other dicarboxylic acid component" include aromatic dicarboxylic acids, alicyclic dicarboxylic acids, aliphatic dicarboxylic acids, polyfunctional acids, and the like. The "other dicarboxylic acid components" may be used alone or in combination of two or more. Among these, from the viewpoint of making the present sealant film easily flexible, the "other dicarboxylic acid component" is preferably an aromatic dicarboxylic acid such as isophthalic acid, 2,6-naphthalenedicarboxylic acid, diphenyldicarboxylic acid, etc., an aliphatic dicarboxylic acid such as adipic acid, sebacic acid, dodecanedioic acid, eicosanoic acid and derivatives thereof, an alicyclic dicarboxylic acid such as 1,4-cyclohexanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, cyclooctanedicarboxylic acid, etc., or a dimer acid. Among these, from the viewpoint of ensuring the desired heat seal strength, it is preferable to contain isophthalic acid and / or sebacic acid.
[0034] In the copolymer polyester A in the sealing layer, the proportion of the "other dicarboxylic acid components" in the total of the dicarboxylic acid components, i.e., terephthalic acid and the "other dicarboxylic acid components" is preferably 15 to 35 mol%, more preferably 17 mol% to 33 mol%, and even more preferably 20 mol% to 30 mol%. When two or more kinds of the "other dicarboxylic acid components" are used in combination, the total amount of them is meant. When the ratio of the "other dicarboxylic acid component" is within the above range, the sealant film can ensure high heat sealability.
[0035] The diol component is not particularly limited, and examples thereof include aliphatic diols such as ethylene glycol, diethylene glycol, trimethylene glycol, tetramethylene glycol, pentamethylene glycol, hexamethylene glycol, octamethylene glycol, decamethylene glycol, neopentyl glycol, 2-ethyl-2-butyl-1,3-propanediol, polyethylene glycol, and polytetramethylene ether glycol. In addition to the above, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, trimethylene glycol, neopentyl glycol, 1,4-cyclohexanedimethanol, bisphenol, and derivatives thereof may also be used. These diol components can be used alone or in combination of two or more, and among these, a combination of ethylene glycol with another alcohol component (such as the above-mentioned diol components) is preferred.
[0036] In addition, when polyester is usually produced (polycondensed) using ethylene glycol as one of the raw materials, a part of the ethylene glycol is modified to become diethylene glycol and is introduced into the polyester skeleton. This diethylene glycol is called by-product diethylene glycol, and the amount of the by-product varies depending on the type of polycondensation (ester exchange method, direct polycondensation), etc., but is about 1 to 5 mol% of the ethylene glycol. In the present invention, diethylene glycol produced as a by-product from ethylene glycol in this way is also included in "other alcohol components".
[0037] Among the above, a particularly preferred copolymer polyester A is a copolymer of terephthalic acid, isophthalic acid, and / or sebacic acid with ethylene glycol and diethylene glycol, in which the proportion of isophthalic acid and / or sebacic acid in the dicarboxylic acid component constituting the copolymer polyester is 15 mol % or more and 35 mol % or less, and the proportion of diethylene glycol in the diol component constituting the copolymer polyester is 0 mol % or more and 5 mol % or less.
[0038] (Resin B) As described above, the sealing layer may be a layer containing a copolymer polyester A and a resin B.
[0039] From the viewpoint of improving the affinity with other layers, it is preferable that resin B contains one or more types of polyester. The polyester (including one or more polyesters) may be a polyester containing terephthalic acid as a dicarboxylic acid component, "other dicarboxylic acid components", and a diol component, in which the ratio of the total content of "other dicarboxylic acid components" to the total content of all dicarboxylic acid components (in the case of containing two or more polyesters, the total of the dicarboxylic acid components contained in each polyester) is 0 mol% or more and 15 mol% or less, preferably 0 mol% or more and 10 mol% or less, and more preferably 0 mol% or more and 5 mol% or less. When the ratio of the "other dicarboxylic acid component" is within the above range, delamination of the sealant film can be prevented. In addition, when the polyester contains ethylene glycol and other alcohol components as diol components, the ratio of the total content of "other alcohol components" to the total content of the diol components (when two or more polyesters are contained, the total of the diol components contained in each polyester) is preferably 0 mol% or more and 5 mol% or less, more preferably 1 mol% or more and 5 mol% or less, and even more preferably 1 mol% or more and 4 mol% or less. When two or more types of "other alcohol components" are used in combination, the total amount means the total amount of the "other alcohol components," and as described above, the "other alcohol components" includes by-produced diethylene glycol. Thus, the polyester constituting Resin B may be a copolymerized polyester containing “another dicarboxylic acid component”, or may be a homopolyester not containing “another dicarboxylic acid component”. Among these, from the viewpoints of heat resistance and film strength, Resin B is preferably polyethylene terephthalate. In this case, the polyethylene terephthalate also contains 1 to 5 mol % of by-produced diethylene glycol.
[0040] In the sealing layer, the mass ratio of the copolymer polyester A to the resin B is preferably 70:30 to 95:5, more preferably 75:25 to 90:10, and even more preferably 80:20 to 90:10.
[0041] Therefore, when the sealing layer contains one or more polyesters, it is preferable that the proportion of the total content of "other dicarboxylic acid components" in the total content of dicarboxylic acid components in the total amount of all polyesters contained in the sealing layer is 15 mol% or more and 30 mol% or less. The content of the diol component is not particularly limited. However, when the polyester contains ethylene glycol and other alcohol components as diol components, the proportion of the total content of the "other alcohol components" in the total content of the diol components is preferably 0 mol% or more and 5 mol% or less. When two or more types of "other alcohol components" are used in combination, the term means the total amount of the two or more types, and "other alcohol components" includes by-produced diethylene glycol, as described above. In this case, the ratio of the total content of the "other dicarboxylic acid components" to the total content of the dicarboxylic acid components is preferably 15 to 30 mol%, more preferably 15 mol% to 28 mol%, and even more preferably 15 mol% to 25 mol%. When two or more kinds of "other dicarboxylic acid components" are used in combination, the total amount of them is meant.
[0042] The sealing layer may contain inorganic particles. By including inorganic particles in the sealing layer, it is possible to impart slipperiness and prevent scratches from occurring during each process. Examples of inorganic particles include silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide. The inorganic particles are not particularly limited, but are preferably contained in the sealing layer in an amount of 0 mass % to 0.5 mass %, particularly 0 mass % to 0.4 mass %, and further preferably 0 mass % to 0.3 mass %.
[0043] <Outermost layer> As described above, the sealant film of the present invention is a laminated film having an outermost layer on one side of a seal layer. The outermost layer is a layer that becomes an outer surface when the film is used as a packaging material or the like.
[0044] The outermost layer contains the copolymer polyester A, and has a lower content (mol %) of other dicarboxylic acid components than the sealing layer. That is, in the copolymer polyester A in the outermost layer, the proportion of the "other dicarboxylic acid component" in the total of the dicarboxylic acid components, i.e., terephthalic acid and the "other dicarboxylic acid component" is preferably 15 to 35 mol%, more preferably 17 mol% to 33 mol%, and even more preferably 20 mol% to 30 mol%. When two or more kinds of the "other dicarboxylic acid components" are used in combination, the total amount of them is meant.
[0045] In the copolymerized polyester A in the outermost layer, the content of the diol component is not particularly limited, but when the copolymerized polyester A contains ethylene glycol and other alcohol components as the diol components, the proportion of the "other alcohol components" in the diol components, i.e., the total of ethylene glycol and the "other alcohol components", is preferably 0 mol% or more and 5 mol% or less, more preferably 1 mol% or more and 5 mol% or less, and even more preferably 1 mol% or more and 4 mol% or less. When two or more types of "other alcohol components" are used in combination, the "other alcohol components" refers to the total amount of the two or more types, and as mentioned above, the "other alcohol components" includes by-produced diethylene glycol.
[0046] An especially preferred example of the copolymer polyester A in the outermost layer is the above-mentioned copolymer polyester Aa, which is a copolymer of terephthalic acid, isophthalic acid, and / or sebacic acid with ethylene glycol and diethylene glycol, in which the proportion of isophthalic acid and / or sebacic acid in the dicarboxylic acid component constituting the copolymer polyester is 15 mol % or more and 35 mol % or less, and the proportion of diethylene glycol in the alcohol component constituting the copolymer polyester is 0 mol % or more and 5 mol % or less.
[0047] The outermost layer may be composed of only the copolymer polyester A, but preferably contains a resin B other than the copolymer polyester A.
[0048] Moreover, it is preferable that resin B in the outermost layer contains one or more types of polyester. The polyester (including one or more polyesters) includes a polyester that contains terephthalic acid as a dicarboxylic acid component, "other dicarboxylic acid components", and a diol component, and in which the ratio of the total content of "other dicarboxylic acid components" to the total content of all dicarboxylic acid components (in the case of containing two or more polyesters, the total of the dicarboxylic acid components contained in each polyester) is 0 mol% or more and 15 mol% or less, preferably 0 mol% or more and 10 mol% or less, and more preferably 0 mol% or more and 5 mol% or less. In addition, when the polyester contains ethylene glycol and other alcohol components as diol components, the ratio of the total content of "other alcohol components" to the total content of the diol components (when two or more polyesters are contained, the total of the alcohol components contained in each polyester) is preferably 0 mol% or more and 5 mol% or less, more preferably 1 mol% or more and 5 mol% or less, and even more preferably 1 mol% or more and 4 mol% or less. When two or more types of "other alcohol components" are used in combination, the total amount means the total amount of the "other alcohol components," and as described above, the "other alcohol components" includes by-produced diethylene glycol. The polyester constituting resin B may be a copolymer polyester containing "another dicarboxylic acid component" or a homopolyester not containing "another dicarboxylic acid component". Among them, from the viewpoint of heat resistance and film strength, resin B is preferably polyethylene terephthalate. In this case, polyethylene terephthalate also contains 1 to 5 mol % of by-produced diethylene glycol.
[0049] In the outermost layer, the mass ratio of the copolymer polyester A to the resin B is preferably from 10:90 to 70:30, more preferably from 15:85 to 65:35, and even more preferably from 15:85 to 60:40.
[0050] Therefore, when the outermost layer contains one or more polyesters, it is preferable that the proportion of the total content of "other dicarboxylic acid components" in the total content of dicarboxylic acid components in the total amount of all polyesters contained in the outermost layer is 3 mol% or more and 15 mol% or less. The content of the diol component is not particularly limited. However, when the polyester contains ethylene glycol and other alcohol components as diol components, the proportion of the total content of the "other alcohol components" in the total content of the diol components is preferably 0 mol% or more and 5 mol% or less. Furthermore, when two or more types of "other alcohol components" are used in combination, the term means the total amount of the two or more types, and "other alcohol components" includes by-produced diethylene glycol, as described above. In this case, the ratio of the total content of the "other dicarboxylic acid components" to the total content of the dicarboxylic acid components is preferably 3 to 15 mol%, more preferably 4 mol% to 14 mol%, and even more preferably 5 mol% to 13 mol%. When two or more kinds of "other dicarboxylic acid components" are used in combination, the total amount of them is meant.
[0051] The outermost layer may contain inorganic particles. By including inorganic particles in the outermost layer, it is possible to impart slipperiness and prevent scratches from occurring during each process. Examples of inorganic particles include silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide. The inorganic particles are not particularly limited, but are preferably contained in the outermost layer in an amount of 0 to 0.5% by mass, particularly 0 to 0.4% by mass, and further preferably 0 to 0.3% by mass.
[0052] <Middle Class> As described above, the sealant film may have at least one intermediate layer between the seal layer and the outermost layer. The intermediate layer may be one layer, or may be two, three, four, or more layers. The intermediate layer preferably contains the copolymer polyester A described above. When an intermediate layer is provided, it is preferable that the content (mol %) of the other dicarboxylic acid component in the sealing layer is higher than that in the intermediate layer. It is also preferable that the content (mol %) of the other dicarboxylic acid component in the intermediate layer is the same as or higher than that in the outermost layer. When multiple intermediate layers are provided, the layering arrangement is such that the content (mol %) of other dicarboxylic acid components in each layer decreases in the thickness direction of the film from the seal layer to the outermost layer, and adjacent intermediate layers may have the same content.
[0053] The intermediate layer may be composed of only the copolymer polyester A, but preferably contains a resin B other than the copolymer polyester A.
[0054] In the copolymer polyester A in the intermediate layer, the proportion of the "other dicarboxylic acid components" in the total of the dicarboxylic acid components, i.e., terephthalic acid and the "other dicarboxylic acid components", is preferably 15 to 35 mol%, more preferably 17 mol% to 33 mol%, and even more preferably 20 mol% to 30 mol%. When two or more kinds of the "other dicarboxylic acid components" are used in combination, the total amount of them is meant.
[0055] In the copolymerized polyester A in the intermediate layer, the content of the diol component is not particularly limited, but when the copolymerized polyester A contains ethylene glycol and other alcohol components as the diol components, the proportion of the "other alcohol components" in the diol component, i.e., the total of ethylene glycol and the "other alcohol components", is preferably 0 mol% or more and 5 mol% or less, more preferably 1 mol% or more and 5 mol% or less, and even more preferably 1 mol% or more and 4 mol% or less. When two or more types of "other alcohol components" are used in combination, the "other alcohol components" refers to the total amount of the two or more types, and as mentioned above, the "other alcohol components" includes by-produced diethylene glycol.
[0056] An especially preferred example of the copolymer polyester A in the intermediate layer is the above-mentioned copolymer polyester Aa, which is a copolymer of terephthalic acid, isophthalic acid, and / or sebacic acid with ethylene glycol and diethylene glycol, in which the proportion of isophthalic acid and / or sebacic acid in the dicarboxylic acid component constituting the copolymer polyester is 15 mol % or more and 35 mol % or less, and the proportion of diethylene glycol in the alcohol component constituting the copolymer polyester is 1 mol % or more and 5 mol % or less.
[0057] Moreover, it is preferable that resin B in the intermediate layer contains one or more types of polyester. The polyester (including one or more polyesters) includes a polyester that contains terephthalic acid as a dicarboxylic acid component, "other dicarboxylic acid components", and a diol component, and in which the ratio of the total content of "other dicarboxylic acid components" to the total content of all dicarboxylic acid components (in the case of containing two or more polyesters, the total of the dicarboxylic acid components contained in each polyester) is 0 mol% or more and 15 mol% or less, preferably 0 mol% or more and 10 mol% or less, and more preferably 0 mol% or more and 5 mol% or less. In addition, when the polyester contains ethylene glycol and other alcohol components as diol components, the ratio of the total content of "other alcohol components" to the total content of the diol components (when two or more polyesters are contained, the total of the alcohol components contained in each polyester) is preferably 0 mol% or more and 5 mol% or less, more preferably 1 mol% or more and 5 mol% or less, and even more preferably 1 mol% or more and 4 mol% or less. When two or more types of "other alcohol components" are used in combination, the total amount means the total amount of the "other alcohol components," and as described above, the "other alcohol components" includes by-produced diethylene glycol. The polyester constituting resin B may be a copolymer polyester containing "another dicarboxylic acid component" or a homopolyester not containing "another dicarboxylic acid component". Among them, from the viewpoint of heat resistance and film strength, resin B is preferably polyethylene terephthalate. In this case, polyethylene terephthalate also contains 1 to 5 mol % of by-produced diethylene glycol.
[0058] In the intermediate layer, the mass ratio of the copolymer polyester A to the resin B is preferably 30:70 to 70:30, more preferably 40:60 to 60:40, and even more preferably 45:55 to 55:45.
[0059] Therefore, when the intermediate layer contains one or more polyesters, it is preferable that the proportion of the total content of "other dicarboxylic acid components" in the total content of dicarboxylic acid components in the total amount of all polyesters contained in the intermediate layer is 10 mol% or more and 20 mol% or less. The content of the diol component is not particularly limited. However, when the polyester contains ethylene glycol and other alcohol components as diol components, the proportion of the total content of the "other alcohol components" in the total content of the diol components is preferably 0 mol% or more and 5 mol% or less. Furthermore, when two or more types of "other alcohol components" are used in combination, the term means the total amount of the two or more types, and "other alcohol components" includes by-produced diethylene glycol, as described above. In this case, the ratio of the total content of the "other dicarboxylic acid components" to the total content of the dicarboxylic acid components is preferably 10 to 20 mol%, more preferably 10 mol% to 19 mol%, and even more preferably 10 mol% to 18 mol%. When two or more kinds of "other dicarboxylic acid components" are used in combination, the total amount of them is meant.
[0060] <Other layers> A barrier layer may be provided on the outermost layer. In addition, another layer may be present between the sealant film and the barrier layer. The barrier layer is a layer that can enhance the property of suppressing gas permeation (also referred to as "gas barrier property"), particularly the water vapor barrier property.
[0061] The inorganic substance serving as the main material constituting the present barrier layer may be, for example, one or more inorganic compounds selected from the group consisting of silicon oxide, silicon nitride, silicon oxynitride, silicon oxycarbide, silicon oxycarbonitride, aluminum oxide, aluminum nitride, aluminum oxynitride, and aluminum oxycarbide.
[0062] Preferred examples of this barrier layer include a PVD inorganic layer formed by a physical vapor deposition (PVD) method, a plasma-assisted deposition inorganic layer formed by a plasma-assisted deposition method, a CVD inorganic layer formed by a chemical vapor deposition (CVD) method, and a coated inorganic layer formed by a method in which inorganic particles are dispersed in an organic polymer and applied.
[0063] The barrier layer may be of a single layer construction or a multi-layer construction of two or more layers. For example, an example of a multi-layer structure having two or more layers can be one in which one layer is an inorganic layer consisting of only an inorganic material, such as an inorganic oxide, and the other layer is an inorganic-organic mixed layer consisting of an inorganic material, such as an inorganic oxide, and an organic material. By mixing an organic material with an inorganic material, a relatively flexible layer can be obtained, and thus the provision of such a flexible layer may improve the gas barrier properties. That is, the coarse protrusions of the base film may cause minute defects called pinholes on the surface of the inorganic layer, or the raw material may fly in clumps during heating and vapor deposition and adhere to the surface of the inorganic layer, causing minute defects. The gas may pass through the gaps caused by these defects, resulting in a decrease in gas barrier properties. Therefore, by laminating the flexible layer as described above on the surface, the defects may be filled, and the gas barrier properties may be improved.
[0064] The thickness of the barrier layer (the total thickness of the inorganic layers when the inorganic layers are multi-layered) is preferably 0.1 to 500 nm, more preferably 1 nm or more or 300 nm or less, and even more preferably 5 nm or more or 100 nm or less. If the thickness of the present barrier layer is within the above range, it is possible to ensure the desired gas barrier properties.
[0065] <Thickness of this sealant film> The thickness of the sealant film is not particularly limited, and an appropriate thickness can be selected depending on the application. From the viewpoint of ensuring high heat sealability and performing barrier deposition and printing processing, the total thickness of the sealant film is preferably more than 3 μm, more preferably 5 μm or more, and even more preferably 10 μm or more. On the other hand, the upper limit of the total thickness of the present sealant film is not particularly limited, but is preferably 200 μm or less, more preferably 160 μm or less, even more preferably 140 μm or less, and even more preferably 120 μm or less.
[0066] The thickness of the sealing layer is not particularly limited, but is preferably from 1 μm to 15 μm, more preferably from 3 μm to 12 μm, and further preferably from 5 μm to 10 μm. The thickness of the outermost layer is not particularly limited, but is preferably from 1 μm to 15 μm, more preferably from 3 μm to 12 μm, and even more preferably from 5 μm to 10 μm. The total thickness of the intermediate layer is not particularly limited, but is preferably from 10 μm to 150 μm, more preferably from 15 μm to 100 μm, and even more preferably from 20 μm to 80 μm.
[0067] <Physical properties of this sealant film> <Heat seal strength> The sealant film preferably has a heat seal strength of more than 25 N / 15 mm when heat sealed at 0.2 MPa for 1 second in the range of 160°C to 200°C. In addition, the range of 160° C. to 200° C. referred to here means any temperature within the range. If the heat seal strength is high even in the high temperature range of 160° C. or higher, it can be suitably used for high-temperature sterilization of retort foods and the like.
[0068] When the heat seal strength exceeds 25N / 15mm, for example, when used as a packaging material, it can contribute to improving the airtightness, and can also be used for heavy-duty and antibacterial purposes. From this viewpoint, the heat seal strength of the sealant film is preferably 26 N / 15 mm or more, more preferably 27 N / 15 mm or more, and even more preferably 28 N / 15 mm or more. The upper limit of the heat seal strength is not particularly limited, but is preferably 80N / 15mm or less, more preferably 75N / 15mm or less, and even more preferably 70N / 15mm or less. The heat seal strength can be measured, for example, by the method shown in the examples described later.
[0069] Furthermore, when heat-sealed at 0.2 MPa for 1 second in the range of 140°C or higher and lower than 160°C and / or greater than 200°C and less than 220°C, the heat seal strength is preferably 15 N / 15 mm or more, more preferably 20 N / 15 mm or more, even more preferably 25 N / 15 mm or more, and particularly preferably 30 N / 15 mm or more.
[0070] <Breaking strength> The sealant film preferably has a breaking strength of 50 MPa or more in both the machine direction (MD) and the transverse direction (TD). By ensuring that the breaking strength is in the range of 50 MPa or more, for example, when used as a packaging material, breaking can be prevented. From this viewpoint, the breaking strength of the sealant film is preferably 50 MPa or more, more preferably 60 MPa or more, and even more preferably 65 MPa or more. The higher the breaking strength, the better, but even if it is 150 MPa or less, it can be said that it is sufficient for practical use. The breaking strength can be measured, for example, by the method shown in the examples described later.
[0071] <Puncture strength> The sealant film preferably has a puncture strength of 150 N / mm or more. By ensuring that the puncture strength is in the range of 150 N / mm or more, for example, when used as a packaging material, the puncture resistance can be improved. From this viewpoint, the sealant film preferably has a puncture strength of 150 N / mm or more, more preferably 155 N / mm or more, and even more preferably 160 N / mm or more. The higher the puncture strength, the better, but even if it is 250 N / mm or less, it can be said that it is sufficient for practical use. The puncture strength can be measured, for example, by the method shown in the examples described later.
[0072] <Shrinkage rate> The present sealant film preferably has a shrinkage rate of -5% to 5% in both the machine direction (MD) and the transverse direction (TD). By keeping the shrinkage rate within the range of -5% to 5%, for example, the original shape can be maintained even in a high temperature environment. From this viewpoint, the shrinkage rate of the present sealant film is preferably −5% to 5%, more preferably −4% to 4%, and even more preferably −3% to 3%. The shrinkage rate can be measured, for example, by the method shown in the examples described later.
[0073] <Haze> The sealant film preferably has a haze of 1% to 15%. By keeping the haze in the range of 1% to 15%, for example, when used as a packaging material, the contents can be visually confirmed. The lower the haze, the higher the transparency, which is preferable, but the lower limit at the current technical level is 1%. From this viewpoint, the haze of the sealant film is preferably 1% to 15%, more preferably 1% to 13%, and even more preferably 1% to 10%. The haze can be measured, for example, by the method shown in the examples described later.
[0074] <Method of manufacturing the sealant film> As an example of the method for producing the sealant film, a case in which the sealant film is a biaxially stretched film will be described below, although the method is not limited to the method described here.
[0075] First, using a known method, raw materials, such as polyester chips, are fed into a melt extrusion device, heated above the melting point of each polymer, the molten polymer is extruded through a die, and cooled and solidified on a rotating cooling drum to a temperature below the glass transition point of the polymer, thereby obtaining an unoriented sheet in a substantially amorphous state. Next, the unoriented sheet is stretched in one direction by a roll or tenter type stretching machine, at a stretching temperature of usually 25 to 120° C., preferably 35 to 100° C., and a stretching ratio of usually 2.5 to 7 times, preferably 2.8 to 6 times. Then, the film is stretched in a direction perpendicular to the first-stage stretching direction at a temperature of usually 50 to 140° C. and a stretch ratio of usually 3.0 to 7 times, preferably 3.5 to 6 times. Then, the film is subsequently heat-set at a temperature of 130 to 270° C. under tension or under relaxation of 30% or less, to obtain the present sealant film as a biaxially oriented film. In the above-mentioned stretching, a method in which the stretching in one direction is carried out in two or more stages can also be adopted.
[0076] After coextrusion, the sealant film may be stretched and heat-set as an integral film as described above. In this case, when the copolymer polyester A is crystalline, the heat setting is preferably carried out at a temperature higher than the melting point of the copolymer polyester A.
[0077] <Applications of this sealant film> The sealant film can be suitably used as a component of packaging materials and the like. The present sealant film may be used as a packaging material as it is, or may be made into a laminate having the present sealant film as at least one layer, and the laminate may be used as at least a part of a packaging material.
[0078] <Explanation of terms, etc.> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film".
[0079] In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES
[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples without departing from the gist of the present invention.
[0081] <Evaluation method> (1) Heat seal strength measurement The heat seal strength was measured according to JIS Z 1707. The sealed surfaces of the films were aligned, and the heat sealed portion was cut to a width of 15 mm at 0.2 MPa, 1 second, and each temperature (160 to 200°C), and the peel strength of the sealed portion was measured using a tensile tester at a pulling speed of 300 mm / min.
[0082] (2) Breaking strength measurement A 1.5 cm x 15 cm sample film was pulled at a speed of 200 mm / min using a tensile tester, and the strength at which the sample broke (fractured) (the tensile load value divided by the cross-sectional area of the test piece) was recorded as the breaking strength (MPa).
[0083] (3) Piercing strength test The puncture strength (N) was measured in accordance with JIS Z1707, and the value obtained by dividing the puncture strength (N) by the film thickness was taken as the unit puncture strength (N / mm).
[0084] (4) Shrinkage measurement A sample film of 1.5 cm x 15 cm was heat-treated for 5 minutes in a hot air oven maintained at a specified temperature (100°C) in an untensioned state, and the length of the sample film was measured before and after the treatment, and calculated using the following formula 1. The measurements were made in both the machine direction (MD) and the cross direction (TD) of the film. Shrinkage rate (%) = {(sample length before heat treatment) - (sample length after heat treatment)} ÷ (sample length before heat treatment) × 100 (Equation 1)
[0085] (5) Haze measurement The measurement was performed using a haze meter DH-2000 manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS K7136.
[0086] <Materials used> [Preparation of polyester raw materials] The composition of each polyester used in the present invention is shown in Table 1. In Table 1, TPA is terephthalic acid, IPA is isophthalic acid, EG is ethylene glycol, and DEG is diethylene glycol. In addition, when producing the polyester (B), SiO2 (SL310 manufactured by Fuji Silysia) was added as a lubricant at a ratio of 6000 ppm to the polyester.
[0087] [Table 1]
[0088] Example 1 The raw materials for the outermost layer were polyester A, polyester B and polyester C mixed in a mass ratio of 25:50:25, the raw materials for the intermediate layer were polyester A and polyester C mixed in a mass ratio of 50:50, and the raw materials for the sealing layer were polyester B and polyester C mixed in a mass ratio of 15:85. The mixed raw materials for the outermost layer, intermediate layer, and seal layer were each fed into a separate twin-screw extruder, and the mixed raw materials for the outermost layer and intermediate layer were melted at 280°C, and the mixed raw material for the seal layer was melted at 270°C. Each was co-extruded onto a cooling roll set at 15°C and cooled and solidified to obtain an unstretched laminated film with three types and three layers (outermost layer / intermediate layer / seal layer). Next, the obtained unstretched laminated film was stretched 3.3 times in the machine direction (MD) at 85° C. using a roll stretching machine. Furthermore, after preheating at 95° C. in a tenter, it was stretched 4.2 times in the transverse direction (TD) at 110° C. Finally, it was heat-treated at 225° C. to obtain a laminated film with a thickness of 36 μm (outermost layer: 10 μm, intermediate layer: 55 μm, seal layer: 10 μm). The properties of the obtained laminated film were evaluated by the above-mentioned methods. The evaluation results are shown in Table 2.
[0089] Example 2 As the raw material for the outermost layer, polyester B and polyester C were mixed in a mass ratio of 50:50. The raw material mass ratios and film-forming conditions for each layer other than the outermost layer were the same as in Example 1, to obtain a laminated film. The evaluation results are shown in Table 2.
[0090] Comparative Example 1 As the raw materials for the intermediate layer, polyester A and polyester C were mixed in a mass ratio of 60:40. The raw material mass ratios and film-forming conditions for each layer other than the intermediate layer were the same as in Example 2, to obtain a laminated film. The evaluation results are shown in Table 2.
[0091] [Table 2] [Industrial Applicability]
[0092] The copolymer polyester sealant film of the present invention has excellent heat seal strength. Furthermore, the copolymer polyester sealant film of the present invention has low shrinkage and excellent mechanical properties such as breaking strength and puncture strength. Therefore, according to the present invention, by laminating another polyester-based base film such as a transparent barrier vapor-deposited PET or by combining a high barrier vapor deposition / printing processing technology with a polyester-based film, a packaging material made of a single material system consisting of polyester can be realized, and a packaging material with excellent recyclability can be provided.
Claims
1. A laminated film consisting of at least two layers, the laminate having a sealing layer and an outermost layer provided directly on one side of the sealing layer, Each layer contains a copolymer polyester made of a copolymer of terephthalic acid and other dicarboxylic acid components and a diol component, the laminated film has a laminated structure in which the content ratio (mol %) of the other dicarboxylic acid component in each layer decreases from the seal layer to the outermost layer, In the total amount of all polyester components contained in the seal layer, the content ratio of the other dicarboxylic acid components to the total content of dicarboxylic acid components is 15 mol % or more and 30 mol % or less, In the total amount of all polyester components contained in the outermost layer, a content ratio of the other dicarboxylic acid components to a total content of dicarboxylic acid components is 3 mol % or more and 15 mol % or less, The copolymer polyester sealant film has a heat seal strength exceeding 25 N / 15 mm when the laminated film is sealed at 0.2 MPa for 1 second in the range of 160 to 200°C.
2. A laminated film having at least three layers, the laminated film having a sealing layer and an outermost layer, and having one or more intermediate layers between the sealing layer and the outermost layer, Each layer contains a copolymer polyester made of a copolymer of terephthalic acid and other dicarboxylic acid components and a diol component, In the total amount of all polyester components contained in the seal layer, the content ratio of the other dicarboxylic acid components to the total content of dicarboxylic acid components is 15 mol % or more and 30 mol % or less, In the total amount of all polyester components contained in the outermost layer, a content ratio of the other dicarboxylic acid components to a total content of dicarboxylic acid components is 3 mol % or more and 15 mol % or less, the content (mol %) of the other dicarboxylic acid component contained in the seal layer is higher than the content (mol %) of the other dicarboxylic acid component contained in the intermediate layer; the content (mol %) of the other dicarboxylic acid component contained in the intermediate layer is equal to or higher than the content (mol %) of the other dicarboxylic acid component contained in the outermost layer; The copolymer polyester sealant film has a heat seal strength exceeding 25 N / 15 mm when the laminated film is sealed at 0.2 MPa for 1 second in the range of 160 to 200°C.
3. A copolymerized polyester sealant film as described in Claim 2, wherein the content ratio of the other dicarboxylic acid components to the total content of dicarboxylic acid components in the total amount of all polyester components contained in the intermediate layer is 10 mol% or more and 20 mol% or less.
4. A copolymer polyester sealant film as described in claim 2 or 3, wherein the sealing layer has a thickness of 1 to 15 μm, the outermost layer has a thickness of 1 to 15 μm, and the intermediate layer has a thickness of 10 to 150 μm.
5. The copolymer polyester sealant film according to any one of claims 2 to 4, wherein the intermediate layer contains polyethylene terephthalate.
6. The copolymer polyester sealant film according to any one of claims 1 to 5, wherein the other dicarboxylic acid component comprises isophthalic acid and / or sebacic acid.
7. The copolymer polyester sealant film according to any one of claims 1 to 6, wherein the outermost layer contains inorganic particles.
8. The copolymer polyester sealant film according to any one of claims 1 to 7, wherein the outermost layer comprises polyethylene terephthalate.
9. A laminate having at least one layer of the copolymer polyester sealant film according to any one of claims 1 to 8.
10. A packaging material having at least a portion thereof the laminate according to claim 9.
Citation Information
Patent Citations
Easy heat-sealability laminated polyester film
JP1991047752A
Multilayered polyester sheet and packaging container produced by working it
JP1997254346A
Polyester film laminated metal panel, method of manufacturing the same, and metal container
JP2001171041A
Polyester laminate
JP2001315284A
Film for wrapping
JP2002256116A